2020
DOI: 10.3390/ijerph17082668
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Cigarette Plain Packaging: Triadic Reactions of Consumers, State Officials, and Tobacco Companies—The Case of Saudi Arabia

Abstract: Objectives: In August 2019, Saudi Arabia started implementing plain packaging for cigarettes. Three months later, an opposing campaign on twitter using an Arabic hashtag “the new smoke” gained momentum amongst smokers. The purpose of this study is to document this opposing campaign’s timeline and describe consumers, government, and tobacco industry rhetoric. Methods: We created a timeline of the campaign events then performed online social listening of Arabic twitter hashtags related to the campaign. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The tobacco industry has vehemently opposed plain packaging,22 23 using multi-jurisdictional strategies including lobbying, organised opposition and front groups, public relations and media campaigns, and litigation 8 24 25. Each country will face its own obstacles, but strong political will, and the coalescing of civil society, advocates, public health and the medical profession can overcome these barriers 26 27.…”
Section: Introductionmentioning
confidence: 99%
“…The tobacco industry has vehemently opposed plain packaging,22 23 using multi-jurisdictional strategies including lobbying, organised opposition and front groups, public relations and media campaigns, and litigation 8 24 25. Each country will face its own obstacles, but strong political will, and the coalescing of civil society, advocates, public health and the medical profession can overcome these barriers 26 27.…”
Section: Introductionmentioning
confidence: 99%
“…A significant association between the concept of plain packaging and the intention to quit smoking was established. Hassounah et al 18 also found that smokers' response to the implementation of plain packaging in Saudi Arabia was strong and loud on both social and traditional media channels. The evidence confirms that plain packaging has an impact on perceived taste and quality.…”
mentioning
confidence: 99%
“…Tobacco smoking causes several chronic diseases, including cancers, lung diseases, and cardiovascular diseases [1][2][3] 4,5 . Consequently, the Saudi government has launched several tobacco control initiatives to combat tobacco smoking 6 . In 2015, an anti-smoking law was enacted in SA to tackle the issue of tobacco use at the national level 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to several countries located in the Eastern Mediterranean region, Saudi Arabia (SA) is witnessing a high prevalence of tobacco use among adults (19.8%) 4 , 5 . Consequently, the Saudi government has launched several tobacco control initiatives to combat tobacco smoking 6 . In 2015, an anti-smoking law was enacted in SA to tackle the issue of tobacco use at the national level 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation